The role of the nursing coordinator and the leadership style in the Italian healthcare organizations - Lupo, Roberto; Lezzi, Alessia; Conte, Luana; Ingrosso, Natascia; Artioli, Giovanna; Botti, Stefano; Leone, Cosimo; Rubbi, Ivan; Carvello, Maicol; Calabrò, Antonino; Vitale, Elsa (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: The leadership of the Nursing Coordinator is essential to ensure quality care and to empower the nursing staff. To identify the leadership style used by the coordinator as nurses and the support staff perceive the leadership behaviors of the coordinator. Methods: Data were collected through an online questionnaire including the Empowering Leadership Questionnaire. Results: Positive associations were recorded between participants’ satisfaction levels and high standards of job performance (p<0.001), being a good example for the whole group (p=0.004) and to encourage sharing ideas and suggestions (p=0.003), hearing ideas and suggestions (p=0.013), giving the opportunity to express their opinions (p=0.046); in the “Coaching” dimension, according to attitudes to help the group to become aware (p<0.001), among all group members (p=0.044); by focusing on their goals (p<0.001); in the “Informing” dimension according to levels and attitudes to explain decisions (p<0.017) and rules and expectations (p=0.046); in the “Showing Concern/Interacting with the Team” dimension according to attitude in personal problems (p<0.028); to discuss concerns (p=0.033); to show interest (p<0.040) and to chat with members (p=0.003). Negative association was registered between the ability to make decisions based solely on the coordinator’s ideas (p=0.010), ability to pay attention to the group’s efforts (p<0.015). Conclusions: The role of the Nursing Coordinator within the work setting is very fundamental. The latter must be able to guarantee, through good leadership, a serene work environment so that professionals can provide optimal care to patients and safeguard their profession.